The effect of service quality, supervision and organizational culture on employee performance at mopah airport - Samperuru, Ones; Ariadi, Wa; Meliala, Janita S (Technium Business and Management, 2024)
The purpose of the study was to determine the effect of service quality, supervision and organizational culture on employee performance at Mopah Airport. The study used a quantitative research approach. The sample of this study was all 130 employees. The results of the questionnaire were tabulated and analyzed using Structural Equation Modeling (SEM) using the SmartPLS application. The results of the analysis proved that service quality and supervision each had an insignificant effect on employee performance. While organizational culture had a significant effect on performance. Furthermore, it was also found that service quality, supervision, and organizational culture simultaneously had an effect on performance.